Interval Endurance and Resistance Training as Part of a Community-Based Secondary Prevention Program for Patients with Diabetes Mellitus and Coronary Artery Disease - Christle, Jeffrey W.; Knapp, Sebastian; Geisberger, Marisa; Cervenka, Marina; Moneghetti, Kegan; Myers, Jonathan; Halle, Martin; Boscheri, Alessandra (Journal of Cardiopulmonary Rehabilitation and Prevention, 2020)
Purpose: High-intensity interval training (HIIT) has been observed to improve health and fitness in patients with cardiovascular disease. High-intensity interval training may not be appropriate in community-based settings. Moderate-intensity interval training (MIIT) and resistance training (RT) are emerging as effective alternatives to HIIT. These have not been well investigated in a community-based cardiac maintenance program. Methods: Patients with coronary artery disease and/or diabetes mellitus participated in clinical examinations and a 6-mo exercise program. Center-based MIIT and home-based moderate continuous intensity exercise were performed for 3-5 d/wk for 30-40 min/session. RT, nutritional counseling, coping, and behavioral change strategies were offered to all patients. Within-group changes in clinical metrics and exercise performance were assessed on a per-protocol basis after 6 mo. Results: Two hundred ninety-two patients (74%) concluded the 6-mo program. There were no serious adverse events. The peak oxygen uptake and peak workload increased significantly, 21.8 ± 6.1 to 22.8 ± 6.3 mL/kg/min and 128 ± 39 to 138 ± 43 W, respectively (both P <.001). Submaximal exercise performance increased from 68 ± 19 to 73 ± 22 W (P <.001). Glycated hemoglobin decreased from 6.57 ± 0.93% to 6.43 ± 0.12%, (P =.023). Daily injected insulin dosage was reduced from 42 IU (interquartile range: 19.0, 60.0) to 26 IU (interquartile range: 0, 40.3, P <.001). Conclusions: MIIT and RT were feasible and effective in a community-based cardiac maintenance program for patients with cardiovascular disease, improving exercise performance, and blood glucose control.
CRIS-Team Scopus Importer:2023-03-08
Keywords: cardiac maintenance program; coronary artery disease; diabetes mellitus; exercise capacity